Lactic and butyric acids, isolated and associated, as alternatives to avilamycin on the immune response of broiler chickens to Newcastle disease - Salazar, Paulo Cesar Riquelme; Do Valle Polycarpo, Gustavo [UNESP]; Dadalt, Julio Cezar; De Assunção Pimenta Ribeiro, Pedro; De Castro Burbarelli, Maria Fernanda; Cruz-Polycarpo, Valquíria Cação [UNESP]; De Albuquerque, Ricardo (UNESP - Universidade Estadual Paulista, 2018)
The objective of this study was to evaluate lactic and butyric acids as alternatives to avilamycin as growth promoters on the immune response of broilers vaccinated against Newcastle disease. Seventy broilers were distributed in a completely randomized design using a 2×2+1 factorial arrangement: presence or absence of lactic acid and butyric acid plus a control treatment with the inclusion of avilamycin, with seven replicates and two birds per experimental unit. Birds were vaccinated against Newcastle disease at 14 days of age. Prior to vaccination (14 days), at 21 and 35 days, blood samples were collected to detect and quantify antibodies against Newcastle disease virus. At 14 and 21 days, there was no significant effect of treatments on antibody titers. At 35 days, the combination of lactic and butyric acids presented a synergistic effect on the immune response of the birds, providing a higher amount of antibody titers compared to the other treatments. The combined effect of lactic and butyric acids improved the immune response of broilers vaccinated against Newcastle disease at 35 days of age, representing a viable alternative to avilamycin.
Keywords: Antibiotic; Antibodies; Immunity; Organic acids; Sanity